Effect of mineral-vitamin premix supplementation on behavioral, performance, hormonal, oxidative stress, and serum biochemical profiles on rutting male Camelus dromedarius in Egypt - Nasreldin, Nani; EL-Shoukary, Ramadan D.; Abdel-Raheem, Ghada S. E.; Gharib, Heba S.; Zigo, František; Farkašová, Zuzana; Rehan, Ibrahim F.; Senosy, Waleed (Frontiers in Veterinary Science, 2023)
The rutting period imposes a stressful condition on male camels, which results in elevated serum cortisol levels and alterations in their sexual behavior. Therefore, the current work was carried out to investigate the effect of mineral-vitamin premix supplementation on behavior, reproductive performance, hormones, serum oxidative stress profile, and other serum biochemical parameters of Camelus dromedaries during the breeding season. Fourteen mature, fertile male Camelus dromedaries were divided into two groups: a control group (n=7) and a mineral-vitamin premix group (n=7). The present study lasted for 95 days during the rutting period (1st February ~ 5th May). Each camel in the premix group received a daily diet of 50 g of mineral-vitamin premix throughout the whole rutting period, during which the frequencies and durations of the following behaviors: maintenance, posture, aggressiveness, and sexual activity were collected every 20 minutes. At the end of the study, blood samples were collected. Results revealed that the premix group showed higher (P < 0.05) maintenance (feeding and rumination), standing, and overall sexual desire-related behavior frequency, besides more times (P < 0.001) for rumination, standing, walking, and lying, while showing lower (P < 0.001) frequencies of overall aggressive behaviors than the control group. The serum concentration of malondialdehyde, nitric oxide, cortisol, blood glucose, and urea evidenced a significant decrease in the premix group compared with the control one, while significantly elevated levels of reduced glutathione, testosterone, total antioxidant capacity, triiodothyronine, and thyroxin, total protein, albumin, globulin, calcium, phosphorus, potassium, and magnesium were recorded in the premix group in comparison with the control. It could be concluded that daily dietary supplementation of 50 g of mineral-vitamin premix to male camels during the breeding season is necessary to overcome the oxidative stress and serum cortisol concentration with a subsequent decrease in aggressive behavior and improvement to testosterone level in blood, body condition score, and body weight gain.